Selection of Comprehensive Assessment Categories Based on the International Classification of Functioning, Disability, and Health for Elderly Patients with Heart Failure: A Delphi Survey among Registered Instructors of Cardiac Rehabilitation. (28th June 2021) - Shiota, Shigehito; Naka, Makiko; Kitagawa, Toshiro; Hidaka, Takayuki; Mio, Naoki; Kanai, Kana; Mochizuki, Mariko; Kimura, Hiroaki; Kihara, Yasuki
Abstract : The development of a comprehensive assessment tool based on the International Classification of Functioning, Disability, and Health (ICF) for elderly patients with heart failure is urgently required. In this study, we classified the ICF categories relevant to heart failure in the elderly through a Delphi survey (3-step questionnaire survey) of 108 Registered Instructors of Cardiac Rehabilitation in the Hiroshima Prefecture. Questionnaires were conducted using postal mail or a web-based platform. The survey was conducted three times, and the survey results were provided as feedback to the participants in the second and third rounds. More than 80% of the respondents selected categories according to the ICF core set methodology. Data were collected from December 2018 to March 2019, with 67, 54, and 46 participants in the first, second, and third rounds, respectively. A total of 58 ICF items were adopted based on the results: 27 body function items, 4 body structure items, 20 activity and participation items, and 7 environmental factor items. This study is characterised by the inclusion of a large number of ICF items for mental function. This result seems to be influenced by the increasing interest in cognitive dysfunction in elderly patients with heart failure. The ICF categories selected for this study allow for a comprehensive assessment of clients for occupational therapy. The findings of this study are expected to provide a basis for an outcome measure to determine the effectiveness of occupational therapy for these patients.